Information as a crucial factor for toilet training by parents. (21st March 2019) - Van Aggelpoel, Tinne; Vermandel, Alexandra; Fraeyman, Jessica; Massart, Michiel; Van Hal, Guido
Abstract: Background: Toilet training (TT) is a milestone in a child's development. Nowadays, children complete TT later than previous generations. This can have detrimental consequences for the child, the parents, and the environment. TT is experienced as difficult and time‐consuming; parents could benefit from guidelines to assist in this process. Methods: Focus group discussions (FGDs) were used to explore parents' experiences in an inductive approach applying purposive sampling. The FGDs aimed to explore the type of information parents wanted to receive on TT, from whom and how. Results: After six FGDs, including 37 participants with personal experience in TT, data saturation was achieved. The findings of this qualitative study show that reputable agencies, family, friends, day‐care workers, and nursery school teachers were considered very helpful and trustworthy sources. TT information should be easily understandable and not contain scientific terms or much text. A colourful and illustrated brochure sent by regular mail is preferred. Conclusion: Our study allows to develop a source of correct and wanted information about TT that parents can and want to use, which helps them completing this training more easily and timely.